Synthesis of biomass-derived N, O-codoped hierarchical porous carbon with large surface area for high-performance supercapacitor. (1st December 2021) - Feng, Tao; Wang, Shunrui; Hua, Yingnan; Zhou, Peng; Liu, Gang; Ji, Kai; Lin, Zhiying; Shi, Shengwei; Jiang, Xingmao; Zhang, Rubing
Highlights: Hierarchical porous carbon was prepared from biomass. Combined KOH/melamine activation is an efficient approach to produce porous structure. The porous carbon shows large specific surface area and high N, O codoping content. The porous carbon-based supercapacitor has high specific capacitance and excellent durability. Abstract: Developing high-performance electrode by use of abundant natural materials as sustainable precursors is extremely important for promoting the practical application of supercapacitors. Herein, we present a promising strategy to convert biomass, sorghum seeds (SS), into efficient electrode material through pre-carbonization and combined KOH/melamine chemical activation. The derived electrode material possesses ultrahigh specific surface area (2132.1 m 2 g −1 ), abundant hierarchical pores, and rich N, O doping, which are very beneficial for energy storage. Typically, the as-prepared carbon displays a high specific capacitance of 536.7 F g −1 at 0.5 A g −1 in 6 M KOH aqueous electrolyte in a three-electrode system. The assembled symmetric supercapacitors offer excellent cycling stability (97.6% retention after 15, 000 cycles) and high specific energy (13.8 Wh kg −1 at specific power of 298.0 W kg −1 ). The study provides a facile, sustainable, and eco-friendly approach to produce hierarchical porous carbon from biomass for high-performance supercapacitors. Graphical abstract: Image, graphical abstract